Impact of source/drain contacts formation of self‐aligned amorphous‐IGZO TFTs on their negative‐bias‐illumination‐stress stabilities. Issue 9 (11th September 2015) - Nag, Manoj; Steudel, Soeren; Smout, Steve; Bhoolokam, Ajay; Genoe, Jan; Cobb, Brian; Kumar, Abhishek; Groeseneken, Guido; Heremans, Paul
Abstract: In this study, we have compared the performance of self‐aligned a‐IGZO thin‐film transistors (TFTs) whereby the source/drain (S/D) region's conductivity enhanced in three different ways, that is, using SiN x interlayer plasma (hydrogen diffusion), using calcium (Ca as reducing metal) and using argon plasma (changing the atomic ratio). All these TFTs show comparable characteristics such as field‐effect mobility ( μ FE ) of over 10.0 cm 2 /(V.s), sub‐threshold slope (SS ‐1 ) of 0.5 V/decade, and current ratio ( I ON / I OFF ) over 10 8 . However, under negative‐bias‐illumination‐stress (NBIS), all these TFTs showed strong degradation. We attributed this NBIS stability issue to the exposed S/D regions and changes in the conductivity of S/D contact regions. The hydrogen plasma‐treated TFTs showed the worst NBIS characteristics. This is linked to increased hydrogen diffusion from the S/D contact regions to the channel. Abstract : In this study, we observed that the negative‐bias‐illumination‐stress stabilities of self‐aligned a‐IGZO thin‐film transistors are strongly dependent upon the source/drain (S/D) region's direct exposure to stress light. Among few different techniques for S/D conductivity enhancements such as metal reduction (Ca metal), Ar plamsa, and SiN x plasma (hydrogen diffusion), the SiN x plasma‐treated thin‐film transistors showed the worst negative‐bias‐illumination‐stress suitabilities. This is linked to increased hydrogen diffusion from the S/D contact regions to the channel.